Pemberdayaan Perempuan sebagai Vulnerable Group dalam Penyebaran HIV/AIDS di Kelurahan Bastiong Kota Ternate - Muliana Muliana (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2021)
The aim of implementing this community service is to increase the knowledge of housewives about preventing HIV/AIDS transmission with ABCD education in Bastiong Karance Village, Ternate City. The method used in the implementation of this activity is women's empowerment in the form of socialization and providing information starting from planning which includes identifying needs, identifying existing potentials and weaknesses, determining ways out of the activities to be carried out, and organizing, implementing, monitoring evaluation and final report preparation. Participants in community service activities are 35 housewives. The results of the community service activities carried out were an increase in the knowledge of housewives in an effort to prevent HIV/AIDS transmission in the Bastiong Karance Village, Ternate City.